Therapeutic Response of Soft Tissue Sarcoma With Novel SS18-POU5F1 Fusion: A Case Report - Liu, Zengjun; Yuan, Hongtu; Han, Mingyong (Frontiers in Oncology, 2021)
A novel SS18-POU5F1 fusion gene was recently reported in soft tissue sarcoma occurring in three adolescent and young adult patients. Herein, we firstly reported the treatment response of SS18-POU5F1 sarcoma to immune checkpoint inhibitor, angiogenesis inhibitor, chemotherapy and radiotherapy. Our patient demonstrated no response to various systemic therapies including immune checkpoint inhibitor, angiogenesis inhibitor and chemotherapy. However, we noted that the SS18-POU5F1 sarcoma had a quick, robust but transient clinical response to radiotherapy. Further studies are needed to elucidate the mechanism underlying the different tumor response to radiotherapy and systemic therapy in this kind of tumor.